A corrupção na arbitragem internacional - Straube, Frederico Gustavo de Souza e (2018)
Corruption is a phenomenon as old as the history of mankind, common to developped countries, as well as to those in development. However, contrary to what happened in the past, it has received greater attention from international organizations and the academic world, mainly because of the collective and universal understanding of its harmful effects on society.International arbitration as a method of dissolving controversies is widely used by private individuals and also by public entities in international relations, especially in commercial trade and investments, and like any and all jurisdictional proceedings, it is not immune to the practice of corruption, whether in the relation between parties and arbitrators, or with witnesses and experts, with a view to subvert law and order in obtaining illicit advantages.Corruption, much more than a question of a cultural nature, is directly related to the efficiency and functioning of the institutions created by society. That is, the present study, without neglecting the influence of cultural factors, such as those in whose cultures are marked by strong patrimonialist bonds, aims at better understanding, describing and suggesting mechanisms of combat and prevention of corruption in order to mitigate a growing sense of mistrust and widespread insecurity in individuals and society as a whole. Thus, this work will seek, through the deductive / descriptive method, to dialogue with the theme and contribute to its problematic through the author's reflection on what he considers an "insufficiency" in the national and international literature, in order to bring some international cases and studies, as well as draw a parallel with Brazilian Law and domestic arbitration